Domination Number in Neutrosophic Soft Graphs - S. Satham Hussain; R. Jahir Hussain; F. Smarandache (Neutrosophic Sets and Systems, 2019)
The soft set theory is a mathematical tool to represent uncertainty, imprecise, and vagueness is often employed in solving decision making problem. It has been widely used to identify irrelevant parameters and make reduction set of parameters for decision making in order to bring out the optimal choices. This manuscript is designed with the concept of neutrosophic soft graph structures. We introduce the domination number of neutrosophic soft graphs and elaborate them with suitable examples by using strength of path and strength of connectedness. Moreover, some remarkable properties of independent domination number, strong neighborhood domination, weights of a dominated graph and strong perfect domination of neutrosophic soft graph is investigated and the proposed concepts are described with suitable examples.